Advanced Prostate Cancer Presenting as Hemolytic Uremic Syndrome - R. Ramos; F. Lopes; T. Rodrigues; N. Rolim; I. Rodrigues; H. Monteiro (Case Reports in Urology)
Introduction. Hemolytic uremic syndrome (HUS) is characterized by endothelial dysfunction, consumption thrombocytopenia, microangiopathic hemolytic anemia, and acute renal failure. HUS generally has a dismal prognosis, except when associated with gastroenteritis caused by verotoxin-producing bacteria. Cancer associated HUS is uncommon, and there are only scarce reports on prostate cancer presenting with HUS. Case Presentation. A 72-year-old man presented to the emergency department with oliguria, hematuria, and hematemesis. Clinical evaluation revealed acute renal failure, hemolysis, normal blood-clotting studies, and prostate-specific antigen value of 1000 ng/mL. The patient was started on hemodialysis, ultrafiltration with plasma exchange, and androgen blockade with bicalutamide and completely recovered from HUS. The authors review the 14 published cases on this association. Conclusion. The association of HUS and prostate cancer occurs more frequently in patients with high-grade, clinically advanced prostate cancer. When readily recognized and appropriately treated, HUS does not seem to worsen prognosis in prostate cancer patients.